Treating Child Sexual Abuse in Family, Group and Clinical Settings Culturally Intelligent Practice for Caribbean and International Contexts - D. Jones, Adele; Trotman Jemmott, Ena; Da Breo, Hazel; Maharaj, Priya (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2016)
XIX, 336 p. 34 illus. in color.